Therapeutic effects of enrofloxacin on pneumonic and diarrhoeic calves - Kürşat Turgut; Osman Erganiş; Abdullah Başoğlu (Eurasian Journal of Veterinary Sciences)
The therapeutic efficacy of Enrofloxacin (Bay-tril;Bayer) against respiratory disease and diarrhoea in 60 neonatal calves was investigated in fieldtrial. Nasal and tracheal flushing samples from calves with pneumonia and rectal samples from calves with diarrhoea were taken for microbiologica examination. Microbiologic isolation from tracheal flushing samples could not be succed in 10 out of 30 pneumonic calves. After sampling, treatment of calves with baytril, initial subcutaneus application (2.5 mg/kg b.w., 10% sol.) followed by oral treatment (2.5 mg/kg b.w. 10% sol.) for three successive days was performed. P. haemolytica (70%) and mycoplasma ssp (30%) in calves with pneumonia and E.coli (86.6%) in calves with diarrhoea were the most common isolated bacteria. Except for 3 calves with pneumonia and 6 calves with diarrhoea, all calves cured by the treatment. In conclusion, Baytril was found to be highly effective in the treatment of pneumonic and diarrhoeic calves.